Sensory Churros Analysis Effect of Mocaf Flour Substitution - Anni Faridah; Septiwi Yuhelma (Media Pendidikan Gizi dan Kuliner, 2023)
Churros is a type of pastry made from water, butter, eggs, sugar, salt and wheat flour. The raw material for wheat flour is wheat which is an imported material. To reduce the need for wheat flour, this study aims to analyze the sensory churros of the influence of mocaf flour substitution as much as 25%, 50%, 75%, and 100%. This type of research is a pure experiment with a completely randomized design (CRD). The data used is primary data obtained directly from 5 expert panelists who gave answers from a questionnaire (organoleptic test format) on the mocaf flour sensory churros. The place and time of the research was carried out on 01-24 December 2021 at the Catering Workshop, Department of Family Welfare, Faculty of Tourism and Hospitality, Padang State University. The data that has been obtained is then tabulated in tabular form and an Analysis of Variance (ANOVA) is performed. If the analysis of variance shows Fcount Ftable, then it is continued with Duncan's test. The results showed that there was a significant effect of substitution of mocaf flour between 25%, 50%, 75% and 100% on sensory churros, namely the soft inner texture sensory. Sensory uniform shape, jagged shape with a length of 10 cm, brown color, fragrant aroma, crunchy texture, sweet taste, and savory skin taste had no effect on sensory churros. The results of the sensory churros test for mocaf flour were the best in treatment X2 with 50% mocaf flour substitution. The results showed that there was a significant effect of substitution of mocaf flour between 25%, 50%, 75% and 100% on sensory churros, namely the soft inner texture sensory. Sensory uniform shape, jagged shape with a length of 10 cm, brown color, fragrant aroma, crunchy texture, sweet taste, and savory skin taste had no effect on sensory churros. The results of the sensory churros test for mocaf flour were the best in treatment X2 with 50% mocaf flour substitution. The results showed that there was a significant effect of substitution of mocaf flour between 25%, 50%, 75% and 100% on sensory churros, namely the soft inner texture sensory. Sensory uniform shape, jagged shape with a length of 10 cm, brown color, fragrant aroma, crunchy texture, sweet taste, and savory skin taste had no effect on sensory churros. The results of the sensory churros test for mocaf flour were the best in treatment X2 with 50% mocaf flour substitution.